Protecting Your Family from Unintentional Poisoning - Donna Davis (EDIS, 2012)
“In 2004, more than 2.4 million exposures to human toxins were reported to poison control centers in the United States. Almost all of them occurred in homes, and 85% percent of poison exposures were unintentional. More than half of them involved children under six years old. As a parent, that is a very frightening statistic.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.